Sleep disturbance in children with attention-deficit hyperactivity disorder: relationship with melatonin and behavior - de Souza, Ana Luiza Decanini Miranda [UNESP] (2024)
Aim: To evaluate the prevalence and types of sleep problems and their correlations with melatonin content and behavior in Attention-Deficit Hyperactivity Disorder (ADHD) children. Method: Sleep in ADHD children and typically developing children (TD) aged 6–14 was assessed by the Sleep Disorders Scale for Children (SDSC) and actigraphy, salivary melatonin quantified by ELISA, and behavior was analyzed using the Strengths and Difficulties Questionnaire. Results: ADHD children showed a higher frequency of sleep disturbances, higher sleep latency, and lower sleep efficiency than in the TD group. The ADHD group presented lower melatonin nocturnal content compared to the TD group. Disorders of Initiating and Maintaining Sleep (DIMS) was moderately associated with nocturnal melatonin. The total behavior difficulties were correlated with Disorders of Initiating and Maintaining Sleep (DIMS), Sleep/Wake Transition Disorders (SWTD), Disorders of Excessive Somnolence (DES), Sleep Hyperhidrosis (SHY) and Total SDSC Score. The behavior was the only determinant of the total SDSC score (R2 = 0.499; p < 0.002). Conclusion: This study provides, for the first time, evidence that among the frequent sleep disturbances in ADHD, the disorders in initiating and maintaining sleep are associated with the low levels of melatonin found in this population. Additionally, these, along with other sleep disturbances, are linked to behavioral problems in ADHD.